2020
DOI: 10.1016/j.ophtha.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Clinical Trial of the Low-Concentration Atropine for Myopia Progression (LAMP) Study

Abstract: Purpose: To evaluate the efficacy and safety of 0.05%, 0.025%, and 0.01% atropine eye drops over 2 years to determine which is the optimal concentration for longer-term myopia control.Design: Randomized, double-masked trial extended from the Low-Concentration Atropine for Myopia Progression (LAMP) Study.Participants: Three hundred eighty-three of 438 children (87%) aged 4 to 12 years with myopia of at least e1.0 diopter (D) originally randomized to receive atropine 0.05%, 0.025%, 0.01%, or placebo once daily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
266
10
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(309 citation statements)
references
References 19 publications
25
266
10
8
Order By: Relevance
“…The findings of the present study, which are supported by observations made in a previous investigation, may suggest that EGF and members of the EGFR family, such as amphiregulin, are some of the substances that were positively or negatively associated with the development of experimental myopia in previous studies. These substances include dopamine, acetylcholine, and other molecules from the cholinergic system and GABAergic system, insulin, glucagon, glucagon‐like peptide‐1, basic fibroblast growth factor, transforming growth factor beta, vasoactive intestinal polypeptide, retinoic acid, nitric oxide, and sonic hedgehog as well as molecules derived from genes like the FBJ osteosarcoma oncogene and immediate early genes 14‐35 . Experimental investigations and clinical randomized trials have shown that atropine eye drops applied in low concentrations reduce the rate of myopization 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the present study, which are supported by observations made in a previous investigation, may suggest that EGF and members of the EGFR family, such as amphiregulin, are some of the substances that were positively or negatively associated with the development of experimental myopia in previous studies. These substances include dopamine, acetylcholine, and other molecules from the cholinergic system and GABAergic system, insulin, glucagon, glucagon‐like peptide‐1, basic fibroblast growth factor, transforming growth factor beta, vasoactive intestinal polypeptide, retinoic acid, nitric oxide, and sonic hedgehog as well as molecules derived from genes like the FBJ osteosarcoma oncogene and immediate early genes 14‐35 . Experimental investigations and clinical randomized trials have shown that atropine eye drops applied in low concentrations reduce the rate of myopization 35 .…”
Section: Discussionmentioning
confidence: 99%
“…These substances include dopamine, acetylcholine, and other molecules from the cholinergic system and GABAergic system, insulin, glucagon, glucagon‐like peptide‐1, basic fibroblast growth factor, transforming growth factor beta, vasoactive intestinal polypeptide, retinoic acid, nitric oxide, and sonic hedgehog as well as molecules derived from genes like the FBJ osteosarcoma oncogene and immediate early genes 14‐35 . Experimental investigations and clinical randomized trials have shown that atropine eye drops applied in low concentrations reduce the rate of myopization 35 . In guinea pigs, tree shrews and in monkeys, the anticholinergic agent pirenzepine, which has a high affinity for the muscarinic M1 receptor, selectivity decreases axial elongation when intraocularly applied 26,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Various concentrations of atropine eye drops have been investigated, and a concentration-dependent effect was observed for both their clinical efficacy as well as adverse side effects. [21][22][23][24][25][26] In spite of reports of their effectiveness in slowing axial elongation, the use of 0.1%, 0.5%, and 1% atropine was not well-accepted due to concentration-dependent side effects, including light sensitivity, reduced near vision and a significant rebound effect after discontinuation. [21][22][23][24][25] Although it was reported that 0.01% atropine could effectively slow myopia progression in terms of refractive error, with negligible side effects, neither a 1year nor 2-year application of 0.01% atropine significantly retarded axial elongation.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] However, a recent study showed the effective, safe performance of other low concentrations (0.05%, 0.025%) of atropine eye drops over two years, but the longer-term outcomes have not been published. 26 Based on these studies, the optimal concentration of atropine, which balances long-term safety and effectiveness, remains to be determined. Currently, 0.01% atropine is the most commonly agent used in East Asia, especially in Taiwan and Singapore.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a higher concentration atropine has been intended for children who showed poor response to 0.01% atropine. In LAMP2 study [19], the e cacy of 0.05% atropine on myopia control was twice that of 0.01% atropine. However, 0.05% atropine induced 2 D accommodative amplitude loss and 1.25 mm pupil dilation, not favorable in terms of long-term safety.…”
Section: Introductionmentioning
confidence: 91%